Peran Kader Posyandu Dalam Meningkatan Status Gizi Balita Dan Pencegahan Stanting Pada Balita, Serta Mengedukasi Gizi Pada Ibu Hamil (Studi Kasus Posyandu Percut Sei Tuan) - Khairunnisa Ritonga; Putri Nurhida Harahap; Putra Apriadi Siregar (Journal of Innovative and Creativity, 2025)
This study examines the role of Posyandu cadres in improving the nutritional status of toddlers and educating pregnant women in Percut Sei Tuan District. With a descriptive qualitative approach, the study involved cadres, pregnant women, mothers of toddlers, and health workers as informants. The results showed that cadres were active in growth monitoring, nutrition counseling, and pregnancy checks, with the support of KKN students. The main obstacles were limited facilities, minimal training, low community participation, and workload without incentives. The study emphasized the need for systematic support from the government and the community to optimize the role of Posyandu cadres